ปัญหาการจัดการศึกษาระบบทวิภาคีประเภทช่างอุตสาหกรรมของ สถาบันอาชีวศึกษา สังกัดสำนักงานคณะกรรมการการอาชีวศึกษา ในเขตจังหวัดสกลนคร - เสนาช่วย, ราชัญ (Journal of Graduate School Sakon Nakhon Rajabhat University, 2017)
ปัญหาการจัดการศึกษาระบบทวิภาคีประเภทช่างอุตสาหกรรมของสถาบันอาชีวศึกษา สังกัดสำนักงานคณะกรรมการการอาชีวศึกษาในเขตจังหวัดสกลนคร DUAL VOCATIONAL TRAINING MANAGEMENT’S PROBLEMS OF THE INDUSTRIAL TECHNICIANS IN THE VOCATIONAL EDUCATION INSTITUTES UNDER THE JURISDICTION OF SAKON NAKHON VOCATIONAL EDUCATION COMMISSION บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาและเปรียบเทียบปัญหาการจัดการศึกษาระบบทวิภาคีประเภทช่างอุตสาหกรรม ของสถาบันอาชีวศึกษา สังกัดสำนักงานคณะกรรมการการอาชีวศึกษาในเขต จังหวัดสกลนคร กลุ่มตัวอย่างที่ใช้ในการวิจัย คือ ผู้บริหารสถานศึกษา ผู้บริหารสถานประกอบการ ครูผู้สอน ครูฝึก และนักศึกษา จำนวน 222 คน โดยใช้วิธีการสุ่มแบบแบ่งชั้น และการสุ่มอย่างง่าย เครื่องมือที่ใช้ในการวิจัยเป็นแบบสอบถามปัญหาการจัดการศึกษาระบบทวิภาคี สถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ ความถี่ ร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน ค่าที (t-test) และวิเคราะห์ความแปรปรวนทางเดียว (One-way Anova หรือ F-test) ผลการวิจัยสรุปได้ดังนี้ 1. ปัญหาการจัดการศึกษาระบบทวิภาคีประเภทช่างอุตสาหกรรม ทั้งรายด้านและโดยรวมอยู่ในระดับน้อย 1.1 ปัญหาการจัดการศึกษาระบบทวิภาคีประเภทช่างอุตสาหกรรม ตามความคิดเห็นของผู้บริหารสถานศึกษา ผู้บริหารสถานประกอบการ ทั้ง 6 ด้าน คือ ด้านหลักสูตร ด้านการจัดการเรียนการสอน ด้านการประชาสัมพันธ์และการประสานงาน ด้านการนิเทศการศึกษา ด้านเครื่องมือเครื่องจักรและสื่อการเรียนการสอน และด้านการวัดและประเมินผล มีความคิดเห็นเกี่ยวกับปัญหาการจัดการศึกษาระบบทวิภาคี โดยรวมอยู่ในระดับน้อย 1.2 ปัญหาการจัดการศึกษาระบบทวิภาคีประเภทช่างอุตสาหกรรม ตามความคิดเห็นของครูผู้สอนและครูฝึก ทั้ง 6 ด้าน คือ ด้านหลักสูตร ด้านการจัดการเรียนการสอน ด้านการประชาสัมพันธ์และการประสานงาน ด้านการนิเทศการศึกษา ด้านเครื่องมือเครื่องจักรและสื่อการเรียนการสอน และด้านการวัดและประเมินผล มีความคิดเห็นเกี่ยวกับปัญหาการจัดการศึกษาระบบทวิภาคี โดยรวมอยู่ในระดับน้อย 1.3 ปัญหาการจัดการศึกษาระบบทวิภาคีประเภทช่างอุตสาหกรรม ตามความคิดเห็นของนักศึกษา ทั้ง 6 ด้าน คือ ด้านหลักสูตร ด้านการจัดการเรียนการสอน ด้านการประชาสัมพันธ์และการประสานงาน ด้านการนิเทศการศึกษา ด้านเครื่องมือเครื่องจักรและสื่อการเรียนการสอน และด้านการวัดและประเมินผล มีความคิดเห็นเกี่ยวกับปัญหาการจัดการศึกษาระบบทวิภาคี โดยรวมอยู่ในระดับน้อย 2. ผลการเปรียบเทียบปัญหาการจัดการศึกษาระบบทวิภาคีประเภทช่างอุตสาหกรรม ของสถาบันอาชีวศึกษา สังกัดสำนักงานคณะกรรมการการอาชีวศึกษาในเขต จังหวัดสกลนคร ตามความคิดเห็นของผู้บริหารสถานศึกษาและผู้บริหารสถานประกอบการ ครูผู้สอนและครูฝึก และนักศึกษา จำแนกตามสถานภาพ พบว่า ทั้งรายด้านและโดยรวมไม่แตกต่างกันอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 ABSTRACT This study was conducted in order to investigate and compare the problems of managing the dual vocational training of the industrial technicians in the vocational education institutes under the jurisdiction of the Office of Sakon Nakhon Vocational Education Commission. The total 222 subjects included the administrators, teachers, trainers, and students. They were obtained through stratified random sampling and simple random sampling. The instrument was a questionnaire to survey the respondents’ opinions on problems of managing dual vocational training. The statistics deviation, t-test, One-way ANOVA or F-test. The study unveiled these results: 1. The problems of managing the dual vocational training of the industrial technicians, as a whole and on each aspect, were at the low level. 1.1 According to the administrators, the problems of managing the dual vocational training of the industrial technicians were composed of six aspects: curriculum; learning-teaching management; public relations and coordination, supervision; machines and equipment; teaching media; and evaluation and assessment. The administrators the problems of managing the dual vocational training of the industrial technicians, as a whole, were at the low level. 1.2 Both the teachers and the trainers felt that the problems of managing the dual vocational training of the industrial technicians were composed of six aspects: curriculum; leaning-teaching management; public relations and evaluation and assessment. They thought that the problems of managing the dual vocational training of the industrial technicians, as a whole, were at the low level. 1.3 Regarding the students, they thought that the problems of managing the dual vocational training of the industrial technicians were also composed of six aspects: curriculum; leaning-teaching management; public relations and coordination, supervision; machines and equipment; teaching media; and evaluation and assessment. The students viewed that the problems of managing the dual vocational training of the industrial technician, as a whole, were at low level, too. 2. When comparing the administrators, entrepreneurs, teachers, trainers, and students’ opinions on the problems of managing the dual vocational training of the industrial technicians in the vocational institutes of Sakon Nakhon vocational Commission based on their statuses, it was found that their opinions did not statistically differ at .05 level of significance.